Features Of Geometry In 2R5 - Mamadaliev B. M (Genius Journals, 2023)
The article is devoted to the study of the geometry of subspaces of a five-dimensional pseudo-Euclidean space. This space is attractive because all kinds of semi-Euclidean, semi-pseudo-Euclidean, hyperbolic three-dimensional spaces with projective metrics are realized in its subspaces. In the sphere of the imaginary radius of space, de Sitter space is realized. An interpretation of de Sitter space in a four-dimensional pseudo-Euclidean space is proved
Keywords: Five-dimensional pseudo-Euclidean; radius; hyperbolic geometry